INTRODUCING A MULTI-LEVEL GOVERNANCE PHASE FRAMEWORK FOR EVENT-LED URBAN DEVELOPMENT FORMATS - Karic, Sarah; Diller, Christian (Erdkunde, 2023)
Events as urban development formats have been relevant strategies for cities for several decades. They may have diverse economic, political, social and ecological effects on the host cities and are accordingly used in a variety of ways and closely linked to urban development and renewal. Complex processes can be identified in the context of the application, planning, implementation and after-use of an event. Furthermore, the planning of events is subject to an extensive multi-level governance of actor constellations and interactions. Against this background, in this paper we introduce a multi-level governance phase framework for formats of event-led urban development in order to create a better understanding of the structures and processes involved. For this purpose, we first use regional garden shows as a case study, which are event formats with a focus on small and medium-sized cities in Germany and on the (further) development of urban green spaces. We then generalize the framework using the governance capacity concept for events and approaches of event-led urban development. The model is well suited to illustrate the relevance of different actors in the process as well as the complexity of diverse processes that occur in the course of event planning. Events als stadtentwicklungspolitische Formate sind seit einigen Jahrzehnten relevante Strategien für Städte. Sie können diverse ökonomische, politische, soziale und ökologische Wirkungen auf die ausrichtenden Städte haben und werden dementsprechend vielfältig genutzt und sind eng mit Stadtentwicklung und Stadterneuerung verknüpft. Im Rahmen der Bewerbung, Planung, Durchführung und Nachnutzung eines Events sind komplexe Prozesse zu identifizieren. Des Weiteren unterliegt die Planung von Events umfangreichen Multi-Level-Governance Akteurskonstellationen und Interaktionen. Vor diesem Hintergrund möchten wir in diesem Paper ein Multi-Level-Governance-Phasenmodell für Formate der eventorientierten Stadtentwicklung einführen, um ein besseres Verständnis für die Strukturen und Prozesse zu schaffen. Dafür nutzen wir als Fallstudie zunächst Landesgartenschauen als Format der ereignisorientierten Stadtentwicklung mit Fokus auf Klein- und Mittelstädte in Deutschland, die sich auf die (Weiter-)Entwicklung von urbanen Grünräumen fokussieren. Anschließend generalisieren wir das Framework mithilfe des Governance Capacity Konzepts für Events und Ansätze der ereignisorientierten Stadtentwicklung. Das Modell eignet sich gut zur Darstellung der Relevanz verschiedener Akteure im Prozess sowie der Komplexität diverser Prozesse, die im Verlauf der Planung von Events auftreten.